Natural resources and civil conflict: The role of military expenditures - Rabah Arezki; Markus Brückner (Journal of Risk and Financial Management, 2021)
Military expenditures significantly affect the relationship between the risk of civil conflict outbreak and natural resources. We show that a significant positive effect of natural resource rents on the risk of civil conflict outbreak is limited to countries with low military expenditures. In countries with high military expenditures, there is no significant effect of natural resource rents on civil conflict onset. An important message is thus that a conflict resource curse is absent in countries with sufficiently large military expenditures.
Keywords: 330; civil conflict; natural resources; military expenditures